PERAN PEREKAM MEDIS DAN INFORMASI KESEHATAN DALAM PELAKSANAAN VAKSINASI COVID-19 MENUNJANG SISTEM INFORMASI KESEHATAN - Indah Aulia Putri (INFOKES (Informasi Kesehatan), 2022)
Health workers have an important role in implementation the Covid-19 vaccination to provide health services in accordance with service standards, professional standards, and standard operating procedures. This study aims to determine the role of PMIK in the implementation of the Covid-19 vaccination to support the health information system at Bhayangkara Tk.II Sartika Asih Hospital Bandung. The research method used is descriptive research method with a qualitative approach. Data collection techniques used are direct observation, interviews and documentation studies. The data taken in this study is the list of daily vaccine administrations and the number of monthly vaccines from March to May 2022. The results of the research show that the role of PMIK in the implementation of Covid-19 vaccination is in accordance with the competency standards that have been set to support the health information system. There were several problems found, namely: 1) The flow of the Covid-19 vaccination implementation which was still using the 4-table flow. 2) at the registration section there are vaccine participants who drop out due to time constraints. Suggestions that can be given are: 1) Hospitals should implement a simplification of the vaccination flow. 2) Good communication between officers and participants of Covid-19 vaccination is required. Keywords: The Role of PMIK, Covid-19 Vaccination, and Health Information System